The assessment of the effect of longitudinal arch support insole on plantar pressure distribution in subjects with flexible flatfoot - Gh. Aminian; M. Farhoodi; Z. Safaeepour; A. Farjad Pezeshk (Afarand Scholarly Publishing Institute, 2012)
Background: The flatfoot might be caused complications and pain within upper joints and also change distribution of plantar foot pressure in flatfoot patients. One of the current treatments for this problem is longitudinal arch support insole which might be used for decreasing the related complications of this disorder. This foot orthosis maybe help to improve the medial longitudinal arch and redistribute of foot plantar pressure. Purpose: Assessing the distribution of plantar foot pressures within flexible flatfoot patients and the effects of longitudinal arch support insole on distribution of plantar foot pressures were the aims of this study. Materials and method: This was a quasi-experimental study with participation of 12 young men with bilateral flexible flat foot (age: 18- 28). The plantar pressures measurement insole (Pedar) was used for measuring the foot plantar pressures as an instrument which it includes five different sizes of insoles with 99 sensors. Each trial included three direct walk ways (nine meters) with normal speed and 50 Hz. There were two types of tests with/without foot orthoses. Results: There was a significant decrease of plantar pressure in medial hindfoot and a significant increase of plantar pressure in midfoot foot by using the longitudinal arch support insole in contrast of without orthoses condition (with shoe). There was also an increasing contact area in the medial part of midfoot foot by using of foot orthosis in comparison of using the shoe only. Conclusion: The results of this study shows that the foot orthoses might be caused to transfer the pressures from other adjacent areas include hindfoot and forefoot to midfoot foot which support the previous studies. Also, significant decrease pressure in hindfoot by using the foot orthoses confirms that insole may help the foot to compensate the function of medial longitudinal arch.